Conservação de animais e o ensino de biologia - Silva, Vinicius Galatti [UNESP]; Vacari, Gabrielle Queiroz [UNESP]; Rodrigues, Beatriz Almeida [UNESP]; Amoroso, Patricia; Santos, Fabiana Cirino dos [UNESP]; Artoni, Silvana Martinez Baraldi [UNESP]; Franzo, Vanessa Sobue; Amoroso, Lizandra [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The PROEX/UNESP Project “Taxidermia de Animais Domésticos e Selvagens” (Taxidermy Domestic and Wildlife) was proposed in order to preserve the exterior of animals through taxidermy technique and present them in schools and in events of course of Biological Sciences, Unesp, Jaboticabal. The project favored understanding of biodiversity and popularization of scientific knowledge in public schools. Also, it resulted in the educational exchange between professors of science and biology in the region, with teachers and students of FCAV, participation in scientific projects and transfer of technical guidelines. Disclosure of taxidermy technique promotes democratization of knowledge and effective participation of the university in society, favoring the improvement of the quality of education.

O projeto PROEX/UNESP “Taxidermia de Animais Domésticos e Selvagens” foi proposto com o objetivo de preservar o exterior dos animais por meio da técnica de taxidermia e apresentá-los em escolas e em eventos do curso de Ciências Biológicas da Unesp, Campus de Jaboticabal. O projeto favoreceu a compreensão da biodiversidade e a popularização do conhecimento científico em escolas públicas. Possibilitou, ainda, o intercâmbio pedagógico entre docentes de Ciências e Biologia da região, com docentes e alunos da FCAV, participação em projetos científicos e repasse de orientações técnicas. A divulgação da técnica de taxidermia promove democratização do conhecimento e participação efetiva da universidade na sociedade, favorecendo a melhoria da qualidade do ensino.
Keywords: Teaching-learning; Environment; Morphology; Ensino-aprendizagem; Meio-ambiente; Morfologia